36+2(-8+3g)=1-g

Simple and best practice solution for 36+2(-8+3g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36+2(-8+3g)=1-g equation:


Simplifying
36 + 2(-8 + 3g) = 1 + -1g
36 + (-8 * 2 + 3g * 2) = 1 + -1g
36 + (-16 + 6g) = 1 + -1g

Combine like terms: 36 + -16 = 20
20 + 6g = 1 + -1g

Solving
20 + 6g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
20 + 6g + g = 1 + -1g + g

Combine like terms: 6g + g = 7g
20 + 7g = 1 + -1g + g

Combine like terms: -1g + g = 0
20 + 7g = 1 + 0
20 + 7g = 1

Add '-20' to each side of the equation.
20 + -20 + 7g = 1 + -20

Combine like terms: 20 + -20 = 0
0 + 7g = 1 + -20
7g = 1 + -20

Combine like terms: 1 + -20 = -19
7g = -19

Divide each side by '7'.
g = -2.714285714

Simplifying
g = -2.714285714

See similar equations:

| 6x+8=3x+15 | | f(7)=5-3x | | Cosx=0.5cosx | | P=x+(4x+3)+(4x+3) | | X^2+4ax+2a=0 | | 4x+12+10x=180 | | 2z(z-3)(z+5)=0 | | 8x=x-16 | | 10-2(x-7)=3x+9 | | a-1=a-12 | | 3x+10y=-78 | | 32x^3-8x^2-4x= | | 45=7x+3-x | | n*cos(2*x)-s*cos(3*x)-s*cos(x)=0 | | -2z+73=3z+24 | | 5c+14+9c=7 | | -5-7x^2=-243 | | 8+4x+x=18 | | .5714285714x+11=15 | | 8(2l+3)=56 | | 4g+2d=11 | | It=v | | 8(1-2a)=40 | | 8-6b^2=-34 | | -132=11y | | -x+11=4x-13 | | -15x+y=25 | | 4.7x+11=15 | | (6+2x)+x=9 | | 25m^2+5=105 | | X^2=4+12 | | 22-5y=16+y |

Equations solver categories